Issues in Recruiting and Retaining Asian American Breast Cancer Survivors in a Technology-Based Intervention Study - Im, Eun-Ok (Cancer Nurs, 2020)
BACKGROUND: Difficulties in recruiting and retaining Asian Americans in traditional research have been well-documented. Despite an increasing number of technology-based cancer studies among racial/ethnic minorities, little is still known about potential issues in recruiting and retaining racial/ethnic minority cancer survivors for technology-based intervention research. OBJECTIVE: This discussion paper aims to examine issues in recruiting and retaining a group of racial/ethnic minorities—Asian American breast cancer survivors—for a technology-based intervention study. METHODS: The parent study is an ongoing large-scale national-scope technology-based intervention study among a target number of 330 Asian American breast cancer survivors. During the recruitment and retention process, research diaries were written by research team members, and the written records of weekly research team meetings were kept. The written records were analyzed using a content analysis. Then, the themes were used to support the discussion points made in the paper. RESULTS: There existed sub-ethnic differences in research participation; it was easier to recruit Chinese participants compared with other sub-ethnic groups. The use of culturally-matched research team members and multiple languages was essential. Gatekeepers were also elemental for recruitment and retention. Various motivation strategies were needed to retain the participants. Each sub-ethnic group used different communication apps. Finally, trust-building was essential to retain the participants in the intervention. CONCLUSIONS: Researchers need to consider these practical issues in future technology-based intervention research. IMPLICATIONS FOR PRACTICE: These issues need to be considered in future program/intervention development and implementation among racial/ethnic minority cancer survivors.